2011
DOI: 10.1089/end.2010.0558
|View full text |Cite
|
Sign up to set email alerts
|

Solo Ultrasonography-Guided Percutanous Nephrolithotomy for Single Stone Pelvis

Abstract: Solo US-guided PCNL can be performed safely as an alternative to the fluoroscopy-guided PCNL for single stone pelvis in a moderately to markedly dilated PCS by an experienced urologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 16 publications
0
35
1
6
Order By: Relevance
“…The proper patient selection, perfect equipment and technique, and accurate follow-up are three considerable points for acceptable results and avoiding significant complications in this modality (6). Key prerequisite for success of PCNL is appropriate renal access.…”
Section: Discussionmentioning
confidence: 99%
“…The proper patient selection, perfect equipment and technique, and accurate follow-up are three considerable points for acceptable results and avoiding significant complications in this modality (6). Key prerequisite for success of PCNL is appropriate renal access.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports about the safety and success of ultrasonography directed renal access or solo-sono PCNL (16, 12). Nevertheless, we could neither find any article describing the success of ultrasonography in targeting the access to the pre-selected calyx nor we could find publications describing the situations regarding renal anatomy or stone morphology that make ultrasonography directed renal PCNL difficult or bothersome.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Despite so many advantages, only a handful of studies have looked at utilizing only US guidance for PCNL. [17][18][19] All of them showed that totally US-guided PCNL was a safe alternative to the traditional fluoroscopic technique. [17][18][19] Despite such encouraging reports, fluoroscopy is still the most commonly used technique as shown by the Clinical Research Office of the Endourological Society (CROES) PCNL data, which reveal that 86.3% of patients 7,8 The present study also demonstrates a similar decline (9 vs 43.8 seconds, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] All of them showed that totally US-guided PCNL was a safe alternative to the traditional fluoroscopic technique. [17][18][19] Despite such encouraging reports, fluoroscopy is still the most commonly used technique as shown by the Clinical Research Office of the Endourological Society (CROES) PCNL data, which reveal that 86.3% of patients 7,8 The present study also demonstrates a similar decline (9 vs 43.8 seconds, p < 0.0001). It does not show any difference in the time taken to achieve the puncture (152.9 vs 144.3 seconds, p = 0.38), which is unlike what was reported in the Basiri study, where the mean duration of access was higher in the ultrasound group (11 vs 5.5 minutes, p = 0.0001).…”
Section: Discussionmentioning
confidence: 99%